Unexpected "Lazarus response" to single-agent bevacizumab in heavily pretreated patients with HER2-positive breast cancer - Alexey V. Emshanov; Denis V. Nesterov; Tatyana N. Sokolova; Priscilla S. Amankwah; Evgeny N. Imyanitov (Open Exploration Publishing Inc., 2023)
Early clinical trials aimed to halt cancer progression by inhibiting the growth of new blood vessels in tumors through single-agent targeted therapy with bevacizumab. These trials largely proved unsuccessful. However, bevacizumab turned out to be efficient when administered in combination with other anticancer drugs. The efficacy of this approach is explained by the ability of bevacizumab to eliminate immature blood vessels thus normalizing intratumoral blood flow and improving the delivery of cytotoxic or targeted agents. This report describes four cases of heavily pretreated patients with metastatic HER2-positive breast cancer, who had no meaningful treatment options left, and who received single-agent bevacizumab as an empirical last-resort therapy. Three of these patients had severe complaints, and they demonstrated striking symptomatic relief within the first day of this treatment. In addition to the observed "Lazarus response", which was likely attributed to the bevacizumab-driven resolution of edema, some evidence of a direct antitumor effect was observed. These data may call for the reconsideration of bevacizumab monotherapy in patients with HER2-associated breast cancer, and perhaps in some other categories of cancer patients.